Feasibility and acceptability of a community pharmacy referral service for suspected lung cancer symptoms. Issue 1 (9th August 2021) - Holland-Hart, Daniella; McCutchan, Grace M; Quinn-Scoggins, Harriet Dorothy; Brain, Kate; Hill, Lucy; Shanbag, Savita; Abel, Michael; White, Kelly; Evans, Angela; Rees, Sarah; Bowen, Sarah; Gemine, Rachel; et al.
Abstract : Background: Lung cancer survival rates in the UK are among the lowest in Europe, principally due to late-stage diagnosis. Alternative routes to earlier diagnosis of lung cancer are needed in socioeconomically deprived communities that are disproportionately affected by poor lung cancer outcomes. We assessed the feasibility and acceptability of a community-based pharmacy referral service to encourage earlier symptomatic referral for chest X-rays. Methods: Seventeen community pharmacies located in a deprived area of Wales participated between March 2019 and March 2020. Stakeholder interviews were conducted with four patients, seven pharmacy professionals and one general practitioner. Four focus groups were conducted, including one with healthcare professionals (n=6) and three with members of the public who were current and former smokers (n=13). Quantitative data regarding patient characteristics and clinical outcomes were collected from hospital records and patient referral questionnaires completed by pharmacists and analysed using descriptive statistics. Qualitative data sets were analysed thematically and triangulated. Results: Twelve patients used the pharmacy referral service, all of whom were male. Average length of the pharmacy consultation was 13 min, with a mean 3 days to accessing chest X-rays in secondary care. Patients experienced a mean 46-day wait for results, with no lung cancer detected. Participants found the service to be acceptable and considered the pharmacy element to be broadly feasible. Perceived barriers included low awareness of the service and concerns about the role and capacity of pharmacists to deliver the service. Facilitators included perceived approachability and accessibility of pharmacists. A well-publicised, multifaceted awareness campaign was recommended. Conclusions: A community pharmacy referral service for lung symptoms was considered an acceptable alternative pathway to symptomatic diagnosis of lung cancer in deprived communities. Wider implementation of the service would require workforce capacity and training to be addressed to ensure optimum utilisation and promotion of the service.